Delayed venous occlusion following embolotherapy of vascular malformations in the brain. - Duckwiler, G R; Dion, J E; Viñuela, F; Reichman, A (American Journal of Neuroradiology, 1992)
PURPOSE To describe the nature and features of delayed venous thrombosis following embolization of arteriovenous fistulae.METHODS Retrospective review of the available clinical history, details of embolization procedures, and results of follow-up angiography were carried out on all embolization procedures performed on high-flow vascular malformations of the brain done at our institution since 1987.RESULTS Four patients were identified who had delayed (greater than 1 week) venous thrombosis/occlusion after embolization of the malformation associated with neurologic complications. Two patients had arteriovenous fistula and two had vein-of-Galen malformations. These patients had no untoward embolization of the venous outlet as a cause of the venous occlusion.CONCLUSIONS It is postulated that thrombosis in the arteriovenous fistula group was induced by conversion (due to embolization) of a patulous high flow venous outlet into a slow flow system; in the vein-of-Galen group, the occlusion was thought to be due to high-flow venopathy.